Gendered Pathways to Integration: Why Immigrants' Naming Practices Differ by the Child's Gender - Jürgen Gerhards; Julia Tuppat (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
We analyze gender differences in immigrants' ethnic boundary making using the example of name giving. We draw on the well-established finding that immigrants are more likely to choose a~name that is common in the host country (strategy of boundary crossing) for female than for male descendants. We distinguish between two dimensions that help us to understand the gender gap in naming: the impact of origin-specific factors (institutionalization of gender equality in the country of origin and religious affiliation) and immigrants' level of integration into the host country. Using data from the German Socio-Economic Panel Study on immigrants from 49~countries, we show that both sets of factors have a~strong impact on immigrants' boundary making in naming, as well as on the extent of the difference between daughters and sons: traditional gender role attitudes foster the gender gap in naming, whereas integration into the host country reduces it.
Keywords: 300; Symbolic boundaries; Boundary making; Assimilation; Gender differences; First names; Symbolische Grenzen; Grenzarbeit; Assimilation; Geschlechterunterschiede; Vornamen